Využití komplexních SW produktů během přípravy a výstavby stavebního díla - Popílková, Kateřina (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Cílem diplomové práce je analýza stavu současných SW produktů používaných ve stavebnictví. Práce je podrobněji zaměřena na SW produkty pro podporu přípravy a realizace stavebních děl. Konkrétně jsou v práci řešeny softwary: KROS plus, BUILDpower, GALA. Analyzována a porovnána je jejich komplexnost, funkčnost, a toho z vyplývající přednosti a nedostatky.

The aim of the master´s thesis is to analyze the current state of software products used in construction. The thesis is specifically focused on software products to support the preparation and realization of building object. Specifically, the thesis deals with software: KROS plus, BUILDpower, GALA. Analyzed and compared to their complexity, functionality, and that the resulting strengths and weaknesses.
Utilization of Complex SW Products during Preparation and Construction of Building Object
Keywords: Investiční projekt; fáze investičního projektu; smluvní vztahy ve výstavbě; SW produkty užívané ve stavebnictví; SW pro přípravu a realizaci stavebního díla; BUILDpower; KROS plus; GALA; analýza SW produktů; funkce SW produktů; Investment project; phase of the investment project; contractual relationships in the construction; SW products used in construction; SW for the preparation and realization of building object; BUILDpower; KROS plus; GALA; analysis of software products; function of software products.